If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 + 3x = 7x Solving 25 + 3x = 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 25 + 3x + -7x = 7x + -7x Combine like terms: 3x + -7x = -4x 25 + -4x = 7x + -7x Combine like terms: 7x + -7x = 0 25 + -4x = 0 Add '-25' to each side of the equation. 25 + -25 + -4x = 0 + -25 Combine like terms: 25 + -25 = 0 0 + -4x = 0 + -25 -4x = 0 + -25 Combine like terms: 0 + -25 = -25 -4x = -25 Divide each side by '-4'. x = 6.25 Simplifying x = 6.25
| a-44=2 | | 4a+7=2a+3 | | 12a+6.2=42.2 | | 2x^2=3x+10 | | r+3=2 | | x+8=-2(2x+2) | | 7(x-2)=4(x-3) | | 22.3=4y+1.5 | | 9d-3.1=14.9 | | 5r+6.3=8.8 | | 9-7m=1-8m | | 85=15r+10 | | -5x=5x+11 | | 3d+14=35 | | 6x=240 | | 3t-2=5(t-4)-2t | | 29-3x=6x+16 | | 0.9(x+90)+0.9x=162 | | 77=10a+7 | | 2(1.5c+4)=1 | | 5(x+1)/4=20 | | 4r+13=41 | | -12(-3x)=72 | | 0.4(x+40)+2.0x=25 | | 22=3r+10 | | -w+2=3w | | 8c-2=14 | | -12(b+12)=-8(b+8)+6b | | -5x=14-5x | | 0.7(x+40)+0.1x=44 | | 5x^2-6x-10=0 | | 5(2x-3)=7(x-2)+16 |